Patriarchal Negotiation: Hegemony of Customs and the Experiences of Sasak Women in the Public and Domestic Spheres - Imam Malik; Sukardi; Ananda Wahidah; Agung Firmansyah; Risma Ade Aryati (Sociology Education, Teaching Training and Education Faculty, Muhammadiyah University of Kupang, 2026)
This research analyzes how patriarchy in Sasak customs is negotiated by women through experiences of safety and comfort in public and domestic spheres. Unlike the view that sees patriarchy as a static cultural structure, this study positions tradition as an arena of power relations that are continuously produced, maintained, and challenged in everyday social practices. Using a mixed-methods approach, qualitative data were collected through phenomenological interviews with Sasak women, while quantitative data were obtained through a Likert-scale survey of 34 respondents. The research results show that women significantly reject certain patriarchal practices, such as early marriage and unconditional obedience, and strongly express support for gender education and cultural change. The pisuke tradition emerges as the most problematic arena because it often causes psychological pressure and marginalizes women's voices. Statistical analysis also shows significant differences based on marital status and education level, where unmarried women and those with higher education levels exhibit a more critical attitude toward patriarchy. These findings affirm that patriarchy in Sasak customs is not monolithic, but rather negotiated across generations, thereby creating space for culturally transformative strategies oriented toward the protection and agency of women